KOMPOSISI ASAM LEMAK DAN KANDUNGAN LOGAM BERAT KECAP BERBAHAN BAKU KEONG SAWAH (Bellamya javanica) - Iin Khusnul Khotimah; Nooryantini Soetikno (Fish Scientiae, 2019)
The purpose of this research is to know the fatty acid composition and heavy metal content of soy sauce snail (Bellamya javanica), which is fermented for seven days with addition of 1.5% bromelin enzyme and papain1% enzyme. The fatty acid composition of soy sauce was analyzed by Chromatography Gas and heavy metal content (Cu and Pb) using AAS. The results showed that the fatty acid component as one of the volatile components in soy bean snacks was identified by 8 types of fatty acids, namely caprylic acid, lauric acid, myristic acid, palmitoleic acid, linoleic acid, linolenic acid anddominated by the components of palmiic acid and stearic acid. The soybean snail saucewith a combination of bromelin enzyme treatment of 1.5% and 1% fermented papain enzyme for seven days showed negative contaminated Cu, but positively polluted by Pb2,285 ppm.